PENGEMBANGAN POS PENYULUHAN DESA: Studi Eksperensial Posluhdes di Desa Pattallassang, Kecamatan Tompobulu, Kabupaten Bantaeng - Jamil, Hatta; Rukka, M. Rusli; Tenriawaru, A Nixia (Jurnal Sosial Ekonomi Pertanian, 2018)
Abstract This research was taking in Pattallassang Village, Tompobulu Sub-distric, Bantaeng District with agrosystem case that is the act of growing and reinforcement the Post of Rural Extention (Posluhdes). The aim of this research to analyze the problem, target and the action to the act of growing and reinforcement of the Posluhdes in The Pattallassang Village, Tompobulu Subdistricy, Bantaeng District. This research used participatory action research method, the researcher activly involve with the informan to comprehend the situation, identify the problem, decide the target and formulate the actions that will take by the board of the Posluhdes. The result of the research showed the primary problems that deal the Posluhdes organitation not working appropriate by the functions yet. This main problem because there are some farmers still push Posluhdes, there is not administration equipment yet, the structure of organization is not represent all of the commodity, and there are not all of the parmers activly invlove in the formulation process of vision and mission. This main problems effecting that the Extentions program in village level is not yet. Based on the problems faced, then formulated the act of development the Posluhdes that is doing sosialitation, increase the tool and infrastructure, prepare operational budget to the organitation, evolving structure and doing sosialitation vision and mission Posluhdes. Keywords: post rural extension; development.